STATE OF THE REAL ESTATE MARKET IN CURRENT CONDITIONS: ANALYSIS OF TRANSFORMATION PROCESSES - Mamonov К.; Goi, V.; Viatkin, R. (Municipal economy of cities. Series: «Economy science», 2025)
It is proven that real estate is one of the important assets that affects the functioning and development of regions, the effectiveness of stakeholder interaction, and the possibilities of land use. Of particular importance is a reliable and complete assessment of real estate, which allows forming a quantitative basis for making informed decisions. The goal has been achieved in terms of determining the state and transformation processes taking place in the real estate market in modern emergency conditions. The tasks solved: substantiation of theoretical provisions on the definition of real estate; determination of areas of real estate market analysis; characterization of ways of real estate valuation, the results of which are used for analyzing the real estate market; establishment of features of regulation of valuation activities; determination of practical aspects of real estate market analysis. A definition of real estate is proposed as an asset that includes land plots, residential and non-residential objects, which is characterized by technical, functional, spatial, urban planning, and environmental parameters around which the underground and above-ground environment is formed and brings a social and economic effect. To manage relations in the system of real estate use, it is proposed to use geographic information systems, which allows automating the processes of its assessment and modeling, taking into account the influence of the presented parameters. As a result of the analysis of the real estate market, the directions of its value growth in all regions have been determined. This indicates the «adaptation» of this market to extraordinary conditions, which are determined by the negative impact of external and internal factors, the consequences of the aggression of the Russian Federation. Low-cost parameters in the «frontline» regions have been established, along with significant prices in the western and some central regions. This indicates significant regional disparities. Directions for the analysis and assessment of real estate use are proposed. The categorical apparatus for determining real estate is substantiated, taking into account the influence of functional, technical, technological, spatial, urban planning, and environmental factors. It is proposed to use geographic information systems as a modern tool to increase the efficiency of real estate use.